Regional food self-sufficiency potential in the European Alpine space - Caroline Pecher; Thomas Marsoner; Erich Tasser (Scientific Reports, 2024)
Abstract The sustainability of the food system needs to be improved, including shortening supply chains and promoting the consumption of regional food. Here, we explore the current potential for regional food self-sufficiency in the European Alpine space by calculating the current regional food/feed energy balance, deriving the regional per capita land footprint based on current food/feed consumption rates, and modelling the current potential for regional food/feed self-sufficiency. We show that 59% of the 560 Pcal of energy currently available in the study area comes from domestic production, and almost 60% of the energy is used for livestock consumption, with high regional variability. The resulting land footprints range from 2301 to 2975 m2 cap−1 y−1. Taking into account changes in cropping patterns, partial intensification, but no expansion of agricultural land, the European Alpine space could produce 89% of its current food demand domestically, with high regional variability due to population density, availability of agricultural land, crop yields, climatic conditions and dietary habits. These findings highlight the potential and limitations of regional mountain food systems and call for new strategies to improve sustainability. Reducing the current high consumption of animal products would reduce the land footprint and increase the potential for food self-sufficiency.